2013
DOI: 10.1371/journal.pone.0054492
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Copy Number Variants Reveals Association of Cilia Genes with Neural Tube Defects

Abstract: BackgroundNeural tube defects (NTDs) are one of the most common birth defects caused by a combination of genetic and environmental factors. Currently, little is known about the genetic basis of NTDs although up to 70% of human NTDs were reported to be attributed to genetic factors. Here we performed genome-wide copy number variants (CNVs) detection in a cohort of Chinese NTD patients in order to exam the potential role of CNVs in the pathogenesis of NTDs.MethodsThe genomic DNA from eighty-five NTD cases and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…Fig. S1A), published previously [Chen, et al., ] was detected in a cranial NTD case. No PARD3 deletions were detected in 274 matched controls and our internal clinical array‐CGH database (Children's Hospital Boston).…”
Section: Resultssupporting
confidence: 78%
“…Fig. S1A), published previously [Chen, et al., ] was detected in a cranial NTD case. No PARD3 deletions were detected in 274 matched controls and our internal clinical array‐CGH database (Children's Hospital Boston).…”
Section: Resultssupporting
confidence: 78%
“…Although some CNVs are found at high frequency in human populations and are thus thought to be a potential source of genetic diversity 2,3 , larger CNVs, especially de novo , are associated frequently with human disorders 4 ; in addition to the documented involvement of CNVs in birth defects (e.g. craniofacial, cardiac, respiratory, renal) 5-12 , CNVs are also understood to be enriched in the pathogenesis of neurodevelopmental and neurocognitive disorders, such as intellectual disability, schizophrenia, and autism spectrum disorders (ASD) 6,13-20 .…”
Section: Introductionmentioning
confidence: 99%
“…Functional studies in human cells and animal systems also showed the requirement for cilia in key developmental signaling pathways, most prominently the Sonic Hedgehog pathway during NT formation (2, 91, 103, 177). In the mouse, approximately 5% of the known NTD genes are related to cilia formation and function, providing a rich source of gene candidates for analysis in human NTD samples that is only beginning to be explored (34). …”
Section: Genetic Regulation Of Neural Tube Closurementioning
confidence: 99%
“…With the decreasing costs of exome and whole-genome sequencing, investigators are beginning to explore the genomes of NTD-affected individuals and families. It is not yet known how copy number variants (CNVs) may contribute to NTDs, beyond a few genetic syndromes associated with NTDs (trisomy for chromosome 3, 18, or the X chromosome) and the recent association between CNVs in cilia genes in NTD samples (34). Protein coding mutations and potential regulatory mutations will likely form the first wave of functional analyses.…”
Section: Genetic Regulation Of Neural Tube Closurementioning
confidence: 99%